Quality of fresh and aged meat from lambs fed peanut meal and glycerin - De Lima Valença, Roberta; Da Silva Sobrinho, Américo Garcia [UNESP]; Romanzini, Eliéder Prates [UNESP]; De Andrade, Nomaiací [UNESP]; Borghi, Thiago Henrique [UNESP]; Zeola, Nivea Maria Brancacci Lopes [UNESP]; Pereira, Mikaele Alexandre; Cirne, Luis Gabriel Alves (Universidade Estadual de Londrina, 2019)
Were evaluated the microbiological and physicochemical characteristics of fresh and aged semimembranosus muscle from 40 uncastrated male Ile de France lambs with 17.15 ± 1.56 kg of initial body weight. Treatments involved fresh and meat aged for 14 days at 4 ºC from lambs receiving four diets, as follows: control; PM - diet with 20% peanut meal replacing soybean meal; G - diet with 25% glycerin replacing corn; and PMG - diet with 10% peanut meal and 12.5% glycerin. The forage:concentrate ratio was 40:60, and corn silage was used as roughage. The diets had similar values of crude protein and metabolizable energy (17.47% and 2.72 Mcal kg/dry matter). A completely randomized design was adopted in a 4×2 factorial arrangement (four diets × fresh and aged meat). Diets and aging did not favor the development of microorganisms in the meat. There was an interaction effect between diets and aging for pH, color, cooking weight loss (CL), and shear force (SF). The fresh meat from animals fed G was lighter compared with the meat from those consuming PM and PMG (lightness of 38.45, 36.26 and 37.88 respectively). Aging increased lightness (37.63 to 40.87), red intensity (15.12 to 15.93), yellow intensity (2.48 to 3.42) and CL (23.84 to 32.59%), reduced pH (5.66 to 5.45), water holding capacity (61.85 to 58.87%) and SF (22.60 to 16.95 N). By-products from biodiesel and peanut production can be used to replace corn and soybean meal in diets for lambs without compromising their meat quality.
Keywords: Aged meat; Biodiesel; By-products; Meat quality; Sheep